Implementasi Telehealth dalam Meningkatkan Perawatan Paliatif pada Pasien Kanker di Era 4.0: Scoping Review - Indy Susanti; Istiqomah Nur Khasanah; Arifin Triyanto (PSIK FKKMK UGM, 2023)
Background: Sustainable palliative care toward advanced stadium cancer is provided by physical, mental, and psychosocial approach. In the 4.0 era along with recent COVID-19 pandemic, the use of telehealth for public service, including for patient with cancer, has increased.Objective: To identify the implementation of telehealth in improving the palliative care of patient with cancer in the 4.0 era.Method: This research was tracing the results of scientific publications using PRISMA flow diagrams. The article selection process was carried out by identification and screening. The searching keywords included Population (cancer patient), Intervention (telehealth OR e-health OR telemedicine OR telenursing OR digital health intervention), Comparison (not applicable), Outcome (improve palliative care in 4.0 era) in several databases, i.e. Google Scholar, Willey Online, Sage, PubMed, BMJ, and Science Direct. Then the articles were selected based on the title, type of article, abstract, and content according to the inclusion and exclusion criteria. Inclusion criteria included topic suitability, published in 2017-2022, in English, open access, and research article.Outcome: Most of the telehealth services were done through mobile applications and website-based consultations. The use of telepalliative showed a positive effect on improving patient self-efficacy, sense of security, patient involvement in care, effectiveness of symptom management, supporting remote care, facilitating access to health professionals. In emergency situations when there was a worsening condition, it was still necessary to carry out direct examination and/or treatment.Conclusion: Telehealth needs further development and research to determine its level of frequency and efficiency to support health services, especially in the field of palliative care.ABSTRAKLatar belakang: Perawatan paliatif berkelanjutan diberikan secara fisik, mental, dan psikososial pada pasien kanker dengan stadium lanjut. Di era 4.0 yang bersamaan dengan adanya pandemi COVID-19, telah meningkatkan penggunaan telehealth dalam pelayanan kesehatan, termasuk pada pasien kanker. Tujuan: Mengetahui implementasi telehealth dalam meningkatkan perawatan pasien kanker di era 4.0. Metode: Penelitian ini dilakukan melalui penelusuran hasil publikasi ilmiah, menggunakan alur diagram PRISMA. Proses pemilihan artikel dilakukan dengan identifikasi dan skrining. Penelusuran kata kunci yang dilakukan, meliputi: Population (cancer patient), Intervention (telehealth OR e-health OR telemedicine OR telenursing OR digital health intervention), Comparison (tidak ada), dan Outcome (improve palliative care in 4.0 era) pada Google Schoolar, Willey Online, Sage, PubMed, BMJ, dan Science Direct. Kemudian artikel diseleksi berdasarkan judul, jenis artikel, abstrak, dan konten sesuai dengan kriteria inklusi dan eksklusi. Kriteria inklusi meliputi kesesuaian topik, diterbitkan tahun 2017- 2022, berbahasa Inggris, open access, dan research article.Hasil: Mayoritas telehealth dilakukan melalui aplikasi seluler maupun konsultasi berbasis website. Pemanfaatan telepaliatif menunjukkan efek positif terhadap peningkatan efikasi diri pasien, rasa aman, keterlibatan pasien dalam perawatan, efektivitas manajemen gejala, pendukung perawatan jarak jauh, dan mempermudah akses kepada profesional kesehatan. Dalam situasi darurat, ketika kondisi memburuk yang membutuhkan konsultasi dan perawatan secara langsung, maka tetap perlu dilakukan pemeriksaan dan/atau perawatan secara langsung.Simpulan: Penggunaan telehealth perlu terus dikembangkan dan diteliti lebih lanjut, untuk mengetahui tingkat frekuensi dan efisiensi pemanfaatannya, dalam rangka mendukung pelayanan kesehatan, khususnya di bidang perawatan paliatif.